Modeling the political choice of public health insurance - Fall, Abdou Khadre Dit Jadir (Frontiers in Applied Mathematics and Statistics, 2023)
This article aimed to study the choice that people have to make between two health insurance systems in a monopolistic scheme. The first health insurance system proposes a uniform contribution level and the second one proposes a contribution level that is proportional to the probability of getting sick. The individuals differ (or are distinguished) by their number in a group, the net income, the contribution level, the probability of getting sick, and health cost. Two kinds of voting models using the welfare function are used; a direct vote that involves a size effect and a probabilistic vote that involves a bias in favor of one system. The results, according to theoretical models, indicate that a uniform contribution level is adopted by high-risk individuals and also if wealth and illness are strongly negatively correlated. However, when wealth and illness are not correlated or are poorly correlated, a contribution proportional to the probability of getting sick is adopted. These results were explained by the fact that the loss of wellbeing for low-income and sick people is more important.